Effect of CrossFit Training versus Resistance Training on Muscular Strength and Body Composition in Sedentary Obese Collegiate Boys - Nithya, Nataraj; Gopalakrishnan, Rathinasamy; Vinosh Kumar, Purushothaman; Mohamed Adam, Shahul Hameed (INTI International University, 2023)
BACKGROUND: The lack of physical activity in daily life induces obesity and increases the risk of diabetes, hypertension and heart disease. Obesity has become a worldwide epidemic that leads to many health-related conditions. Regular exercises can markedly reduce the body weight and fat mass without any dietary caloric restrictions in obese and overweight individuals. OBJECTIVE: To determine the effect of crossfit training versus resistance training on muscular strength and body composition in sedentary obese collegiate boys. METHODS: An experimental study conducted on 20 obese subjects, they were divided into 2 groups of 10 in each group based on the convenient sampling method. Group A underwent Crossfit training and Subjects in Group B underwent Resistance training for 4 weeks. 1 RM Bench press test, 1 RM Squat test and Skinfold thickness measurement were used to measure Upper body muscular strength, Lower body muscular strength and Body composition. RESULTS: An Independent sample t-test was used to compare the two groups. There was a significant difference in Bench press test scores in Group A (1.08 ± 0.05, p = 0.002) and in Group B (1.22 ± 0.03, p = 0.009), t(18)=7.22. Squat test scores in Group A (1.44 ± 0.10, p = 0.016) and Group B (1.21 ± 0.04, p = 0.04), t(18)=6.4. Skinfold thickness measurement scores at the level of Triceps (Group A = 28.4 ± 2.88, p = 0.008 and Group B = 34 ± 3.62, p = 0.006), t(18)=3.8, Chest (Group A = 26.5 ± 3.03, p = 0.021 and Group B = 34.2 ± 4.10, p = 0.027), t(18)=4.8 and Subscapular (Group A = 27.3 ± 3.20, p = 0.005 and Group B = 36.7 ± 4.64, p = 0.03), t(18)=5.3. The results suggest that Crossfit training group have shown significant improvement in all parameters following intervention. CONCLUSION: The study concludes that the Crossfit training is more effective in improving muscular strength and in reducing body composition than resistance training in sedentary obese collegiate boys.